Penerapan Metode Gerak dan Lagu Untuk Meningkatkan Sosial Emosional Anak Usia 5-6 Tahun di RA Al Fajar Denai - Amalia Hasibuan, Citra; Khadijah, Khadijah (Generasi Emas, 2024)
It is very important to implement discipline in early childhood, to train discipline in early childhood in terms of developing social emotions in children. As this research aims to determine the social-emotional development of children aged 5-6 years before the movement and singing methods were implemented at RA Al-Fajar Denai, how the movement and singing methods were implemented at RA al-Fajar Denai to improve the socio-emotive development of children aged 5 -6 years old, and whether movements and singing methods can improve the social emotional development of children aged 5-6 years at RAAl-Fadar Denai. Apart from observations and compilation of supporting materials, this study uses a classroom action research approach. Using a collaboration paradigm that emphasizes cooperation between researchers and teachers, this Classroom Action Study was carried out for two months, from February to March 2024, in Raudhatul Atfhal Al-Fajar Denai, Kec. At RA Al-Fajar Denai, researchers collaborated with group teachers to plan, implement, observe and think about activities during two work cycles. From the research results, which were produced using movement and song as methods, the findings are very relevant to children's social-emotional development. Specifically, the data we obtained showed that 6.7% of children who had previously not progressed and 13.3% of children who had developed as expected had not progressed, and that 20% and 80% of children had developed very well, respectively. achieved the desired category of 65%. We can conclude that the movement and song methods that have been used have a great influence on the social emotional development of children aged 5-6 years. .